Reading Comprehension Assessment Rubric for Foreign Language Level A1 Based on Ger (Gemeinsame Europäische Referenzrahmen) - Yoan Yulitasari; Ahmad Munir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research is to produce an assessment rubric for reading comprehension in German with the standard GER (Gemeinsame europäische Referenzrahmen). This arises because the same standard will make it easier for students and educators to provide qualifications for learning German. The research method taken is qualitative. The technique used in this research is documentation and interviews. The series of assessment rubrics will help make it easier for educators to find out students' weaknesses in language and for students to deepen the knowledge they feel is lacking. Expert validation shows a figure of 97% for this reading comprehension rubric—subjects taken by students of a course institution. Keywords: Foreign Language Level, GER (Gemeinsame europäische Referenzrahmen), Reading comprehension assessment